ANTI-INFLAMMATORY EFFECTS OF Channa micropeltes EXTRACT TOWARDS INTERLEUKIN-10 IN DIABETIC RAT - Amy Nindia Carabelly; Juliyatin Putri Utami; Didit Aspriyanto; Milka Widya Sari; Erika Norfitriyah (FKG Unlam, 2022)
Background: Inhibition of tissue repair is a symptom of prolonged diabetic inflammation that occurs in wounds resulting in delayed healing. Inflammation can be controlled by giving food supplements that have anti-inflammatory properties such as Channa micropeltes (CM). CM has high protein content, including albumin, omega 3 and omega 6 fatty acids, vitamin C, and zinc. Purpose: This study aimed to analyse the effect of the CM extract on the levels of IL-10 in the wound healing process of normal and diabetic rats. Methods: This study was a true experimental design with a post-test-only control group design. The samples were the diabetic model group given CM extract at 16 mL/kg BB dose and negative control group for 14 days. Results: Compared to the control, the concentration of IL-10 in DM group was significantly higher in the DM without CM treatment. Interestingly, we found the level of IL-10 in DM-CM was significantly decreased while the level of TNF-a in DM-CM decreased as well. Conclusion: CM at a dose of 16 mL/kg BW for 14 days in the wound healing process of Wistar rats can increase IL-10 in the normal group but could not increase IL-10 in the diabetic group. Keywords: Anti-inflammatory, Channa micropeltes, Diabetes, Interleukin-10.